Plan de negocios para crear empresa comercializadora de café tostado bajo la marca “Café Saludable” con los beneficios del café verde, en el departamento del Quindío (2013)
The following draft grade was submitted as a BUSINESS PLAN TO CREATE DISTRIBUTOR OF ROASTED COFFEE COMPANY UNDER THE BRAND "HEALTHY COFFEE" WITH BENEFITS OF GREEN COFFE IN THE DEPARTMENT OF QUINDÍO which can observe a different management of coffee, to take advantage of all benefits and medicinal properties, using a mild roasting process which allows the green coffee not to lose its properties. The idea of offering in a market as competitive as is the coffee drink, a product that promises yet traditional novelty to implement a healthy coffee with all its nutrients in traditional flavors such as green coffee, leading it to open doors to other ways of consuming coffee and an additional ingredient as all the nutrients it has the green coffee avoiding the use of synthetic component. Adding to market trends on healthy food products and therefore healthy, it means absent from chemicals. The business plan development will be advanced through the maquila scheme for distribution and sale to stores Naturist houses initially. On the other hand this business plan is presented with the following structure, a first part containing the draft and a second part containing the structure of the business plan first.